Mechanical probing of ferroelectrics at the nanoscale. Issue 40 (3rd October 2019) - Heo, Y.; Sharma, P.; Liu, Y. Y.; Li, J. Y.; Seidel, J.
Abstract : This article reviews AFM-based mechanical probing methods for ferroelectrics and discusses recent developments and future opportunities in this research area. Abstract : Mechanical properties of ferroelectric materials at the nanoscale have received growing interest over the past years due to new developments in scientific instrumentation and novel materials that allow for the study of so far scarcely investigated and/or hidden nanoscale phenomena. The use of atomic force microscopy (AFM) as the main investigation tool has shed new light onto various areas of interest, from non-destructive probing of Young's modulus to mechanically triggered phase transitions at nanoscale regions in ferroelectrics. Together with various theoretical approaches, these scanning probe microscopy based concepts provide a powerful platform for nanoscale mechanical property studies. Here we provide an overview of recent developments and investigations, and give an outlook to future opportunities in this research area.